Application of RULA and REBA to Analyze Body Posture of Assembling Workers (Case Study PT XYZ) - Wahyu Eko Cahyanto; Asep Erik Nugraha; Taufik Akbar Firmansyah (School of Industrial and System Engineering, Telkom University, 2022)
Work productivity can be influenced by body posture or attitude when workers do their work and theconditions of the work environment are less ergonomic. PT. XYZ is an organization participated in theTruck Body industry. Assembling workers at XYZ Company still uses human labor in the welding processor cutting the component assembly process. Jobs with less ergonomic positions can cause fatigue toworkers and are at risk of causing Musculoskeletal Disorders. This study expects to decide the degree ofwork injury in Assembling laborers and is expected to be a recommendation for companies to improvework station conditions. The information taken is as photographs while Assembling laborers go about theirresponsibilities. The review was directed utilizing the Nordic Body Map interview technique, theconsequences of the survey showed grievances to laborers with average score of 63.3. Based on the risklevel classification table, the score is categorized as moderate and needs to be improved. Then furtherinvestigation was done utilizing the REBA and RULA strategies to decide the state of the specialist's bodyact while going about his job. The consequences of the review show that the REBA estimation of thestance of Assembling laborers has a high gamble and requires changes. With respect to the aftereffects ofthe computation of RULA for laborers in the Assembling part of XYZ Company is classified as moderateyet in addition not excessively unsafe and remedial move can be made.